Business resilience system (BRS) : driven through boolean, fuzzy logics and cloud computation : real and near real time analysis and decision making system - Zohuri, Bahman; Moghaddam, Masoud (Springer, 2017)
This book provides a technical approach to a Business Resilience System with its Risk Atom and Processing Data Point based on fuzzy logic and cloud computation in real time. Its purpose and objectives define a clear set of expectations for Organizations and Enterprises so their network system and supply chain are totally resilient and protected against cyber-attacks, manmade threats, and natural disasters. These enterprises include financial, organizational, homeland security, and supply chain operations with multi-point manufacturing across the world. Market shares and marketing advantages are expected to result from the implementation of the system. The collected information and defined objectives form the basis to monitor and analyze the data through cloud computation, and will guarantee the success of their survivability's against any unexpected threats. This book will be useful for advanced undergraduate and graduate students in the field of computer engineering, engineers that work for manufacturing companies, business analysts in retail and e-Commerce, and those working in the defense industry, Information Security, and Information Technology.? Provides a model of Business Resilience System (BRS) to all sectors, including defense, intelligence, and homeland security;? Shows how to implement an intelligent BRS system in place, based on Service Level Agreement (SLA), set by organization stakeholders;? Demonstrates a logical and physical setup of BRS, with its Risk Atom and Processing Data Point (PDP) core;? Presents a comprehensive collection of research on the subject of BRS.
Includes index.
Keywords: Organizational resilience.; Decision making.; elektronické knihy; electronic books